Subjective sleep quality and fatigue assessment in Polish adult patients with primary immunodeficiencies: A pilot study - Grochowalska, Kinga; Ziętkiewicz, Marcin; Więsik-Szewczyk, Ewa; Matyja-Bednarczyk, Aleksandra; Napiórkowska-Baran, Katarzyna; Nowicka-Sauer, Katarzyna; Hajduk, Adam; Sołdacki, Dariusz; Zdrojewski, Zbigniew (Frontiers in Immunology, 2023)
Primary immunodeficiencies (PIDs) are clinically heterogeneous disorders caused by abnormalities in the immune system. However, PIDs are genetically determined and may occur at any age from early childhood to elderly age. Due to chronic patterns, the risk of malignancy and organ damage in patients with PIDs may affect any aspect of life, including sleep patterns. To our knowledge, the prevalence of insomnia and subjective sleep quality have not been investigated in patients with PIDs. Therefore, this pilot study was conducted to investigate sleep quality, the prevalence of sleep disturbances, and fatigue in adult patients with PIDs in Poland. All participants were surveyed using the Athens Insomnia Scale, Pittsburgh Sleep Quality Index, Fatigue Severity Scale, and a questionnaire concerning general health and demographic data. We included 92 participants: 48 women (52.2%) and 44 men (47.8%). Participants’ mean age was 41.9±13.9 years. The mean sleep duration was 7.0±1.5 hours, and the mean sleep latency was 41.2±53.1 minutes. Additionally, 44.6% of patients (n=41) had symptoms of insomnia and 44.6% (n=42) had poor sleep quality. Less than one-fourth (n=22; 23.9%) of the patients reported the use of sleeping pills; moreover, clinically significant fatigue was reported in 52.2% (n=48). Our investigation provides insight into the problem of sleep disturbances in patients with PIDs. Data have demonstrated that sleeping disorders with concomitant fatigue are common in patients with PID. Further studies are needed to determine the determinants of poor sleep quality in this specific group of patients.